2007
DOI: 10.1002/chem.200601883
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Stability of the M‐H‐B Bond in Borane σ Complexes [M(CO)51‐BH2R⋅L)] and [CpMn(CO)21‐BH2R⋅L)] (M=Cr, W; L=Tertiary Amine or Phosphine): Substituent and Lewis Base Effects

Abstract: We investigated the influence of a substituent and a Lewis base on boron upon the thermodynamic stability of metal complexes of borane-Lewis base adducts, [M(CO)5(eta1-BH(2)R.L)] (M=Cr, W) and [CpMn(CO)2(eta1-BH2R.L)], where R=Cl, I, m-C6H4F, Ph, H, Me, Et; L=PMe3, PPh3, NMe3, quinuclidine. In these compounds, the stability of the metal-borane linkage was enhanced by increasing the electron-releasing ability of the substituent on boron. A stronger base L additionally stabilized the complexes. The strength of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
71
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(78 citation statements)
references
References 93 publications
5
71
1
1
Order By: Relevance
“…Table 4 summarizes the T c and DG # values of all the three r-borane complexes. Shimoi and co-workers estimated the free energy of activation (DG # ) for the H-atom scrambling process for the carbonyl rich r-borane complex 3 and found to be 34 kJ/mol at 213 K. Replacement of three Cr-H-B 3c-2e bond [14]. The value is about 28% less than that of the free Me 3 NÁBH 3 , indicating weakening of the B-H r-bond to a certain extent.…”
Section: Variable Temperature Nmr Spectroscopymentioning
confidence: 84%
See 2 more Smart Citations
“…Table 4 summarizes the T c and DG # values of all the three r-borane complexes. Shimoi and co-workers estimated the free energy of activation (DG # ) for the H-atom scrambling process for the carbonyl rich r-borane complex 3 and found to be 34 kJ/mol at 213 K. Replacement of three Cr-H-B 3c-2e bond [14]. The value is about 28% less than that of the free Me 3 NÁBH 3 , indicating weakening of the B-H r-bond to a certain extent.…”
Section: Variable Temperature Nmr Spectroscopymentioning
confidence: 84%
“…It has been previously established that, in r-borane complexes the bound B-H hydrogen atom and the terminal BH 2 hydrogen atoms are involved in fast exchange with each other at ambient temperatures [14]. At room temperature, the time scale of this dynamic process is short so as to observe the signals due to the bound and the terminal B-H hydrogen atoms separately in the NMR spectra.…”
Section: Variable Temperature Nmr Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…(9)) [9,10,18]. Crystal structure analysis of (OC) 5 Cr(H 3 B·PMe 3 ) (8) revealed that the borane-Lewis base adduct interacts with metal center via a B-H bond to give a M-H-B 3c2e bonding.…”
Section: Synthesis and Structure Of H 3 B·l-coordinated -Complexesmentioning
confidence: 99%
“…Manganese complexes Cp(OC) 2 Mn(H 3 B·L) (9; L = PMe 3 , 10; L = NMe 3 , 11; L = quinuclidine) were also prepared by photochemical reaction of CpMn(CO) 3 and H 3 B·L, however, these were isolated in only low yield due to the high lability of borane ligands (Eq. (10)) [18,23]. The interatomic Mn-B distance (9; 2.682(3) Å and 10; 2,573(2) Å) is again significantly longer than those observed in usual Mn-B single bonds (2.06-2.16 Å) [44], indicating negligible interaction between Mn and B.…”
Section: Synthesis and Structure Of H 3 B·l-coordinated -Complexesmentioning
confidence: 99%